Antibacterial and Antimycotic Properties of Modiﬁed Carbon Sorbents - V. T. Dolgikh; L. G. P’yanova; A. V. Lavrenov; E. V. Naumkina; A. V. Sedanova; M. S. Delyagina; D. N. Ogurtsova (Антибиотики и Химиотерапия, 2023)
The aim  of the work was to study the biological activity  of modiﬁers and carbon  sorbent samples modiﬁed by them  in relation to some types of microorganisms.Material and  methods. The carbon  sorbent under  study  and the modiﬁed samples were obtained at the Center of New Chemical Technologies BIC. Glycolic acid, lactic acid, glycine, and glutamic acid were used as modiﬁers. Strains of Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Klebsiella pneumoniae 418, Esherichia coli ATCC 25922, Candida albicans (clinical strain) were used as test cultures. The test sample was placed in the wells of a sterile plate, then a working suspension of the test culture was added in the amount of 2.0 ml until completely wet 1:1. The survival of microorganisms was determined by quantitative inoculation from each well of the «sample — microorganism» mixture on Petri dishes with simple nutrient agar using the sector crop method (Gold). The culture species were conﬁrmed by studying their cultural, morphological, and biochemical properties.Results. The conducted studies have demonstrated high antibacterial and antimycotic activity of carbon  sorbent samples modiﬁed with hydroxyl acids  in relation to the most  common opportunistic pathogens of pyoinﬂammatory diseases of bacterial and fungal  nature  in comparison with the initial  sorbent sample. The carbon  sorbent modiﬁed with lactic  acid oligomer showed the highest antibacterial and antimycotic activity.Conclusion. High antibacterial and antimycotic activity  of carbon  sorbent samples modified with hydroxy  acids  and amino acids in relation to the most common opportunistic pathogens of pyoinflammatory diseases of bacterial and fungal nature  was established in comparison with the initial  sample of the sorbent. The carbon  sorbent sample modified with amino acids has a pronounced antibacterial effect against all studied bacterial test strains, but exhibits weak antimycotic properties. The use of modified carbon  sorbents is a promising direction for the application therapy of pyoinflammatory infections.